VD_FINDINFO HC / 2013 / 74 vom 10. Januar 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, ENFANT NÉ HORS MARIAGE, MESURE PROVISIONNELLE, REVENU HYPOTHÉTIQUE | 285 al. 1 CC, 248 let. d CPC (CH), 303 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)